A arte contemporânea e suas memórias instáveis: a obra 200 Milhões de Anos: Árvore Pedra (2010), de Anna Barros - Dalla Costa, Cristina Landerdahl (2024)
This thesis deals with the updating, preserving, and archiving of the artwork in Nanoart 200 Milhões de Anos: Árvore Pedra (2010) by Brazilian artist Anna Barros (1931-2013). The hypothesis is that it is possible to safeguard a collection of digital works in a university museum, considering the guidelines of a secure chain of custody. The aim is to keep the work suitable for new exhibitions. Oliver Grau's publications are used as a methodological reference on the use of archival topology and memory to establish transformations in the context of museums and contemporary artistic languages. The artwork instalation marks the beginning of the Museu Arte Ciência Tecnologia - MACT/UFSM, collection, whose coordinators are three professors from the areas of Arts, Sciences, and Computer Science. It begins with a brief history of museums and university museums with theoretical references and ICOM guidelines. The starting point is the experience of the Museu de Arte Contemporânea da Universidade de São Paulo (MAC/USP) in the preservation field in university museums, and then the MACT/UFSM, from its beginnings as a project to the inauguration of the physical space. Anna Barros' professional career and some of her artistic projects are examined, tracing her career from graduation to the end of her life. Aspects of nanoscience, nanotechnology, and Nanoart are studied, and Barros' work is related to Robert Pepperell's Visual Indeterminacy and Edgar Morin's concept of complexity Works by Victoria Vesna and James Gimzewski are presented, which were a reference for the Brazilian artist's Nanoart creations, showing some that are preserved in the Archive of Digital Art (ADA). Analog and digital narratives are considered through the Museum I+D+C Research Group at the Universidad Complutense de Madrid, where she did a Doctorate Sandwich Abroad (DSE) internship. These strategies are used to make the exhibition space more inclusive. The work 200 Milhões de Anos: Árvore Pedra (2010) is analyzed, including its characteristics, assembly, and detailing of the pieces. It checks which parts are most vulnerable and places them in a systemic preservation context based on international regulations. We managed to update the work, which is waiting for the university to release the use of the Tainacan to implement its safeguarding. As a contribution, the aim is to maintain social memory, helping to build history through the History of Contemporary Art so that the digital works can be suitable for new exhibitions.